Public good or climate washing?: A guideline for climate and health researchers considering funding from carbon-intensive industries - Hoe, Connie; Bunker, Aditi; Arnés-Sanz, Cristina; Rocklöv, Joacim; Wild, Kirsty; Holmes, Wallis Turner; Woodward, Alistair (The lancet. Planetary health, 2024)
Should climate and health researchers accept funding from industries that profit from climate-damaging consumption? In this Personal View, we aim to ignite discussions on this key topic and to introduce a guideline to possibly help climate and health researchers grappling with this complex question. Drawing from existing tools focused on other public health issues and the conclusions of the 2023 Lancet Series on commercial determinants of health, we propose a guideline comprising six parts: meeting public health and climate goals; building credibility and trust; avoiding undue dependence on particular sources of funding; not inflating without good reason the public image of industry; embedding processes to ensure transparency and independence; and protecting the freedom to publish. We invite other climate and public health scientists to report their own experiences and provide feedback on this guideline.